2003
DOI: 10.1111/j.0014-3820.2003.tb01503.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Selection in Female Perceptual Space: How Female Tungara Frogs Perceive and Respond to Complex Population Variation in Acoustic Mating Signals

Abstract: Abstract. Female preferences for male mating signals are often evaluated on single parameters in isolation or small suites of characters. Most signals, however, are composites of many individual parameters. In this study we quantified multivariate traits in the advertisement call of the tú ngara frog, Physalaemus pustulosus. We represented the calls in multidimensional scaling space and chose nine test calls to represent the range of population variation. We then tested females for phonotactic preference betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 33 publications
0
82
0
Order By: Relevance
“…Ryan & Rand (2003b) studied female mate choice in response to recorded natural calls from males in the study population (Gamboa, Panamá ) and showed that the complex calls of some males are consistently more attractive than those of others. Here we use this natural variation in attractiveness to examine how such intrinsic differences influence the extent to which females commit to a given male in the face of dynamic changes in call complexity.…”
Section: The Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Ryan & Rand (2003b) studied female mate choice in response to recorded natural calls from males in the study population (Gamboa, Panamá ) and showed that the complex calls of some males are consistently more attractive than those of others. Here we use this natural variation in attractiveness to examine how such intrinsic differences influence the extent to which females commit to a given male in the face of dynamic changes in call complexity.…”
Section: The Systemmentioning
confidence: 99%
“…system. Other studies have addressed signal variation within the population (Ryan 1985;Ryan & Rand 2003b). In addition to using the mean synthetic call, we also conducted choice tests with six natural advertisement calls (three whine-chucks, Wc (n1), Wc (n2) and Wc (n3), and the identical three whine-chucks with the chuck digitally excised to leave just the whine, W (n1), W (n2) and W (n3)) recorded from three males in Gamboa, Panamá ( Fig.…”
Section: Stimuli and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Calls were recorded by M. J. Ryan in July 1996 in Gamboa, Panama, with a Marantz PMD 420 cassette recorder and a Sennheiser ME 80 microphone with K3U power module. These calls were also used in the study of Ryan & Rand (2003b).…”
Section: Frog Callsmentioning
confidence: 99%
“…duration, bandwidth, peak frequency) of elements that constitute the acoustic signal, or more obvious shifts in composition of elements of call repertoire (Bee et al, 2001;Ryan & Rand, 2003;Boul et al, 2007;Guerra & Ron, 2008;Rodríguez et al, 2010). Although intraspecifi c variation of discrete elements occurs to some extent among acoustic signals of sympatric males of Neotropical anurans (e.g., Guerra & Ron, 2008;, fi xed diff erences have also been reported among allopatric groups of individuals, and these diff erences have been generally attributed to evolutionary eff ects of isolation by distance or vicariance, potentially reinforced by sexual selection (Boul et al, 2007;Guerra & Ron, 2008;Amézquita et al, 2009).…”
mentioning
confidence: 99%